2006
DOI: 10.1007/s00264-006-0226-4
|View full text |Cite
|
Sign up to set email alerts
|

Effects of screw eccentricity on the initial stability of the acetabular cup

Abstract: One of the major failure modes of cementless acetabular components is the loosening of the acetabular cup, which is mostly attributable to insufficient initial stability. A hemispherical cup with a porous coating which is inserted with press-fit fixation and secured with several screws is one of the most widely used approaches. Many studies have found that bone screws are very helpful aids for cup fixation, but the optimal surgical technique for inserting screws has not been clearly reported. In this study, he… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
28
1

Year Published

2009
2009
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 30 publications
(29 citation statements)
references
References 22 publications
0
28
1
Order By: Relevance
“…Hsu et al [12,13] showed the number of screws applied does not appear to have a significant effect on peak micromotion or the patterns of micromotion distribution from finite element analyses. Kwong et al [14] experimentally investigated the use of one to four screws to fix the acetabular cup, and concluded that addition of supplemental screws did not significantly enhance stability of the implant under pressfit conditions.…”
Section: Discussionmentioning
confidence: 99%
“…Hsu et al [12,13] showed the number of screws applied does not appear to have a significant effect on peak micromotion or the patterns of micromotion distribution from finite element analyses. Kwong et al [14] experimentally investigated the use of one to four screws to fix the acetabular cup, and concluded that addition of supplemental screws did not significantly enhance stability of the implant under pressfit conditions.…”
Section: Discussionmentioning
confidence: 99%
“…Apart from this, Hsu et al . had studied the mechanical effect of press fit cup on the offset and angular eccentric screw in different experimental as well as the computational environment which is not directly associated with these findings 2324. Thus, we sought to determine the effect of the eccentric screw for two angular rotations (17° and 34°), along with different configurations [Table 1].…”
Section: Discussionmentioning
confidence: 99%
“…It is not known, however, how these holes affect both the fixation of our shell or how they affect the surgeon's ability to distinguish good fixation. Previous studies have looked at screw insertion for acetabular shell fixation using Sawbones material [5][6][7] ; however, in our study, we set out to examine the biomechanics of screw insertion through custom burr holes in revision TM shells.…”
Section: Discussionmentioning
confidence: 99%
“…There have, however, been studies performed to validate the use of this material as a substitute for cancellous bone, [8][9][10][11] and many studies have used Sawbones as a substitute for biomechanical testing. [5][6][7]12,13 Its reproducibility during testing is favored for more accurate results. Our study was also limited by the blindfolding of the test subjects.…”
Section: Discussionmentioning
confidence: 99%